Meta-analysis of operative experiences of general surgery trainees during training. Issue 1 (21st December 2016) - Elsey, E J; Griffiths, G; Humes, D J; West, J
Abstract: Background: General surgical training curricula around the world set defined operative numbers to be achieved before completion of training. However, there are few studies reporting total operative experience in training. This systematic review aimed to quantify the published global operative experience at completion of training in general surgery. Methods: Electronic databases were searched systematically for articles in any language relating to operative experience in trainees completing postgraduate general surgical training. Two reviewers independently assessed citations for inclusion using agreed criteria. Studies were assessed for quantitative data in addition to study design and purpose. A meta-analysis was performed using a random-effects model of studies with appropriate data. Results: The search resulted in 1979 titles for review. Of these, 24 studies were eligible for inclusion in the review and data from five studies were used in the meta-analysis. Studies with published data of operative experience at completion of surgical training originated from the USA (19), UK (2), the Netherlands (1), Spain (1) and Thailand (1). Mean total operative experience in training varied from 783 procedures in Thailand to 1915 in the UK. Meta-analysis produced a mean pooled estimate of 1366 (95 per cent c.i. 1026 to 1707) procedures per trainee at completion of training. There was marked heterogeneity between studies ( I 2 = 99·6 per cent). Conclusion: There is a lack of robust data describing the operative experiences of general surgical trainees outside the USA. The number of surgical procedures performed by general surgeons in training varies considerably across the world. Abstract : Varies considerably